A Mesoscopic Simulation for the Early-Age Shrinkage Cracking Process of High Performance Concrete in Bridge Engineering - Guodong Li; Zonglin Wang (Advances in Materials Science and Engineering)
On a mesoscopic level, high performance concrete (HPC) was assumed to be a heterogeneous composite material consisting of aggregates, mortar, and pores. The concrete mesoscopic structure model had been established based on CT image reconstruction. By combining this model with continuum mechanics, damage mechanics, and fracture mechanics, a relatively complete system for concrete mesoscopic mechanics analysis was established to simulate the process of early-age shrinkage cracking in HPC. This process was based on the dispersion crack model. The results indicated that the interface between the aggregate and mortar was the crack point caused by shrinkage cracks in HPC. The locations of early-age shrinkage cracks in HPC were associated with the spacing and the size of the aggregate particle. However, the shrinkage deformation size of the mortar was related to the scope of concrete cracking and was independent of the crack position. Whereas lower water to cement ratios can improve the early strength of concrete, this ratio cannot control early-age shrinkage cracks in HPC.